Nutritional patterns associated with the maintenance of neurocognitive functions and the risk of dementia and Alzheimer's disease: A focus on human studies. (May 2018) - Pistollato, Francesca; Iglesias, Ruben Calderón; Ruiz, Roberto; Aparicio, Silvia; Crespo, Jorge; Lopez, Luis Dzul; Manna, Piera Pia; Giampieri, Francesca; Battino, Maurizio
Graphical abstract: Abstract: Ample epidemiological evidence suggests a strong correlation among diet, lifestyle factors and the onset and consolidation of dementia and Alzheimer's disease (AD). It has been demonstrated that AD, diabetes, obesity, insulin resistance, and cardiovascular disease are strongly interconnected pathologies. Preventive strategies and nutritional interventions seem to be promising approaches to delay neurocognitive decline and reduce the risk of AD and other non-psychiatric co-morbidities. In this regard, healthy dietary patterns, characterized by high intake of plant-based foods, probiotics, antioxidants, soy beans, nuts, and omega-3 polyunsaturated fatty acids, and a low intake of saturated fats, animal-derived proteins, and refined sugars, have been shown to decrease the risk of neurocognitive impairments and eventually the onset of AD. Here we review the role of some nutrients and, in particular, of healthy dietary patterns, such as the Mediterranean diet and other emerging healthy diets, DASH (Dietary Approach to Stop Hypertension) and MIND (Mediterranean-DASH dietIntervention for Neurodegenerative Delay), for the maintenance of cognitive performance, focusing specifically on human studies. The beneficial effects associated with overall diet composition, rather than single nutrient supplementations, for the prevention or the delay of AD and dementia are discussed.